2018
DOI: 10.1097/acm.0000000000002338
|View full text |Cite
|
Sign up to set email alerts
|

Can Maintenance of Certification Work? Associations of MOC and Improvements in Physicians’ Knowledge and Practice

Abstract: Most of the studies included in this review highlighted circumstances in which MOC was associated with positive impacts on physician knowledge and patient care processes or outcomes. Future collaborative research is needed to improve the relevance, helpfulness, and generalizability of continuing certification to different physicians across specialties and practice settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The coding concept "outcomes model" was retrieved from one source only. We mapped the different types of educational outcomes (highlighted in Table 2) to the assessment frameworks of Moore et al, 50 Miller, 74 and Kirkpatrick and Kirkpatrick, 75 as suggested by Price et al 73 The majority (17/37; 46%) of studies targeted program-level followed by individual-level outcomes (12/37; 32%). Eight papers (22%) described both levels of outcomes.…”
Section: Frequency Of Coding Concepts Across the Data Set: Competencymentioning
confidence: 99%
“…The coding concept "outcomes model" was retrieved from one source only. We mapped the different types of educational outcomes (highlighted in Table 2) to the assessment frameworks of Moore et al, 50 Miller, 74 and Kirkpatrick and Kirkpatrick, 75 as suggested by Price et al 73 The majority (17/37; 46%) of studies targeted program-level followed by individual-level outcomes (12/37; 32%). Eight papers (22%) described both levels of outcomes.…”
Section: Frequency Of Coding Concepts Across the Data Set: Competencymentioning
confidence: 99%
“…42 A 2018 review of the literature regarding MOC and activities done for MOC credit (i.e., self-assessment and practice improvement) concluded that most studies showed a positive association between MOC components (i.e., MOC exams, self-assessment activities, practice improvement activities) and physician knowledge, learning, changes in practice, and changes in patient outcomes but acknowledges that findings are concentrated among a few specialty boards, and many studies of activities done for MOC credit (i.e., self-assessment and practice improvement) are based on small local interventions. 43 Our review focused specifically on MOC requirements and included those studies that addressed MOC overall, performance on MOC exams in particular, or other activities done for MOC (i.e., self-assessment and practice improvement). The findings are detailed below.…”
Section: Us Physiciansmentioning
confidence: 99%
“…RPC programme requirements vary from country to country but, typically, involve a combination of learning and assessment elements such as participation in knowledge self-assessments, examinations, quality improvement projects or practice audits, appraisal, peer and patient feedback, and CPD [6, 10, 11]. The debate continues as to whether RPC has been effective in achieving these outcomes [1214].…”
Section: Introductionmentioning
confidence: 99%
“…RPC has been criticised as being a ‘tick-box’ exercise and an unnecessary bureaucratic burden for doctors and employers [6]. Doctors have expressed concerns about RPC programmes’ relevance [16], and ensuring that RPC applies to doctors’ daily practice remains a challenge [14, 15].…”
Section: Introductionmentioning
confidence: 99%